Cap-independent translation and a precisely located RNA sequence enable SARS-CoV-2 to control host translation and escape anti-viral response. Issue 14 (18th July 2022) - Slobodin, Boris; Sehrawat, Urmila; Lev, Anastasia; Hayat, Daniel; Zuckerman, Binyamin; Fraticelli, Davide; Ogran, Ariel; Ben-Shmuel, Amir; Bar-David, Elad; Levy, Haim; Ulitsky, Igor; Dikstein, Rivka
Abstract: Translation of SARS-CoV-2-encoded mRNAs by the host ribosomes is essential for its propagation. Following infection, the early expressed viral protein NSP1 binds the ribosome, represses translation, and induces mRNA degradation, while the host elicits an anti-viral response. The mechanisms enabling viral mRNAs to escape this multifaceted repression remain obscure. Here we show that expression of NSP1 leads to destabilization of multi-exon cellular mRNAs, while intron-less transcripts, such as viral mRNAs and anti-viral interferon genes, remain relatively stable. We identified a conserved and precisely located cap-proximal RNA element devoid of guanosines that confers resistance to NSP1-mediated translation inhibition. Importantly, the primary sequence rather than the secondary structure is critical for protection. We further show that the genomic 5′UTR of SARS-CoV-2 drives cap-independent translation and promotes expression of NSP1 in an eIF4E-independent and Torin1-resistant manner. Upon expression, NSP1 further enhances cap-independent translation. However, the sub-genomic 5′UTRs are highly sensitive to eIF4E availability, rendering viral propagation partially sensitive to Torin1. We conclude that the combined NSP1-mediated degradation of spliced mRNAs and translation inhibition of single-exon genes, along with the unique features present in the viral 5′UTRs, ensure robust expression of viral mRNAs. These features can be exploited as potential therapeutic targets.